The Role of Holland’s Personality Types (Riaces) in Professional Teacher Readiness Among Pre-Service Teacher Education (PPG) Students - Najwa Husniyatin Nadhiroh; Tarsono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study investigates the role of Holland’s personality types (RIASEC) in predicting professional teacher readiness among pre-service teachers enrolled in the Teacher Professional Education Program (PPG), particularly in the Guidance and Counseling specialization. Using a quantitative correlational design, the study involved 30 PPG students selected through total sampling. Data were collected using a Holland Personality Types (RIASEC) inventory and a professional teacher readiness questionnaire, both of which demonstrated satisfactory validity and reliability. Data analysis was conducted using descriptive statistics and linear regression analysis. The results revealed that Holland’s personality types have a significant and positive effect on professional teacher readiness (β = 0.860, p < 0.001), indicating that higher congruence between students’ personality characteristics and the demands of the guidance and counseling profession is associated with higher levels of professional readiness. Furthermore, the coefficient of determination (R² = 0.740) indicates that 74% of the variance in professional teacher readiness can be explained by RIASEC personality types, while the remaining 26% is influenced by other factors beyond the research model. These findings highlight the central role of vocational personality in shaping professional readiness and suggest that integrating personality-based considerations into teacher education programs may enhance the effectiveness of professional preparation for future guidance and counseling teachers.